Upaya Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran PjBL pada Mata Pelajaran Sistem Kendali : Penelitian - Dewi Ummu Karima; Hari Putranto; Arif Wicaksono (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to improve student learning achievement in the subject of Control Systems through the implementation of the Project-Based Learning (PjBL) model in Grade XI Electrical Power Installation Engineering (TITL) at SMK Nasional Malang. The research used the Classroom Action Research (CAR) method with the spiral model of Kemmis and McTaggart, consisting of planning, action, observation, and reflection stages carried out over two cycles. The research subjects were 23 students of Grade XI TITL. Instruments used included cognitive tests, observation sheets, and activity documentation. The results showed a significant improvement in students' cognitive learning mastery. In the pre-cycle, only 4 students achieved mastery, which increased to 14 students in the first cycle and reached 23 students in the second cycle. The implementation of the PjBL model proved effective in enhancing conceptual understanding and encouraging active student engagement. These findings support the idea that project-based learning enables students to build their knowledge through direct experience in solving contextual problems.